PENGARUH ATMOSFER TOKO, PROMOSI PENJUALAN DAN MOTIVASI BELANJA HEDONIS TERHADAP IMPULSE BUYING: Studi Pada Konsumen Carrefour Blok M Square - Enrico Fridhoriyanto, - (2019)
This research is a quantitative that aims to determine the effect of store atmosphere, sales promotion and hedonic shopping motivation to Impulse Buying. Population in this research is visitor of Carrefour Blok M Square. The variables used in this research are store atmosphere, , sales promotion and hedonic shopping motivation independent variable, then Impulse Buying as dependent variable.The sample size was taken 75 respondents, with nonprobability sampling method, especially purposive sampling. Data collection was done through questionnaires. In this research, three hypotheses will be tested using PLS (Partial Least Square) analysis tool.Based on the results of data processing with PLS (Partial Least Square) has the result that (1) store atmosphere has an effect on Impulse Buying with t-statistics of 0.000. (2) sales promotion has an effect on Impulse Buying with a t-statistic value of 0.012. (3) hedonic shopping motivation has no effect on Impulse Buying with t-statistic value of 0,916.